2019
DOI: 10.1080/15384101.2019.1598726
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FENDRR represses proliferation, migration and invasion through suppression of survivin in cholangiocarcinoma cells

Abstract: This study was to investigate the biological function and underlying mechanisms of FENDRR in cholangiocarcinoma (CCA) cell proliferation, migration and invasion. FENDRR and survivin expression in CCA tissues or cell lines were measured by qRT-PCR. In QBC939 and HuCCTl cells, cell proliferation was detected by CCK-8, cell migration and invasion were using transwell assay. RNA pull-down and RIP assay were performed to determine whether FENDRR can combine with SETDB1 in CCA cell. The effect of SETDB1 on survivin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…Fetal-lethal non-coding developmental regulatory RNA (FENDRR) is a new-founded lncRNA which has been reported as a tumor suppressor in different cancers including non-small lung cancer, prostate cancer, breast cancer, cholangiocarcinoma and hepatocellular carcinoma [9][10][11][12]. However, biological effects and its mechanism with respect to CC remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal-lethal non-coding developmental regulatory RNA (FENDRR) is a new-founded lncRNA which has been reported as a tumor suppressor in different cancers including non-small lung cancer, prostate cancer, breast cancer, cholangiocarcinoma and hepatocellular carcinoma [9][10][11][12]. However, biological effects and its mechanism with respect to CC remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Some lncRNAs could be therapeutic or protective against liver diseases or cancer. For example, expression levels of lncRNA-NEF and FENDRR are downregulated in CCA tissues compared to normal tissues (54,60). Overexpression of these lncRNAs inhibited cell migration and invasion of CCA cell lines HuCCT1, QBC939, or TFK-1 cells, indicating the potentials of lncRNA induction as another therapeutic approach for CCA (54,60).…”
Section: Induction Of Lncrna Expressionmentioning
confidence: 99%
“…FENDRR is a lncRNA, which is downregulated in various cancers such as breast cancer, prostate cancer, and hepatocellular carcinoma (57)(58)(59). A study using 60 CCA patients has found that expression of FENDRR is downregulated in CCA tissues compared to non-cancerous tissues, and FENDRR expression is negatively correlated with expression of survivin (60). Survivin is a protein that inhibits apoptosis and upregulated in cancers (61,62).…”
Section: Functional Roles Of Lncrnas In Ccamentioning
confidence: 99%
See 2 more Smart Citations